Medium-temperature matt double-layer transmutation glaze and preparation method thereof
Through the combination formula and firing process of base glaze and surface glaze, the market's demand for medium-temperature matte double-layer kiln-changing glaze is solved, and the matte double-layer kiln-changing glaze is achieved with low lead and cadmium content and good thermal shock resistance, meeting the The market demand for matte or matte kiln-shaped glaze and is suitable for large-scale production.
Patent Information
- Application Number
- CN202411339090.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-09-25
AI Technical Summary
The market lacks medium-temperature matte double-layer kiln-changing glaze, and the existing technology is mainly concentrated in bright double-layer kiln-changing glaze, which is difficult to meet customers' demand for matte or matte kiln-changing glaze.
The base glaze and surface glaze are combined. The base glaze contains boron fuse, potassium feldspar, quartz powder, alumina powder, etc. The surface glaze contains boron fuse, dolomite, titanium dioxide and a small amount of calcium. It is ground by wet ball milling and The firing process forms a matte double-layer kiln-changing glaze with low lead and cadmium content and good thermal shock resistance.
It has achieved a dull double-layer kiln-changing glaze with low lead and cadmium content and good thermal shock resistance, low firing temperature, suitable for large-scale production, and combined artistic and colorful richness to form a product suitable for market demand.
Smart Images

Figure CN119176673A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of daily-use ceramic preparation, and in particular relates to a medium-temperature matte double-layer kiln-changed glaze and a preparation method thereof. Background Art
[0002] The matte double-layer kiln-changed glaze in my country has a special effect and has been missing in the market. The market has always been dominated by ordinary glossy or matte glazes. Gradually, the glossy double-layer kiln-changed glaze series has been developed and is well received by customers. With further feedback from the market, many customers have put forward higher requirements and hope to see some matte or matte kiln-changed glazes. Therefore, this series of reaction kiln-changed glazes has been developed based on actual conditions. The kiln-changed products of these two glazes are well received by the market and are developing rapidly.
[0003] The Chinese patent application with publication number CN113800770A discloses a medium-temperature double-layer kiln-changed glaze and a production method. The base glaze of the medium-temperature double-layer kiln-changed glaze includes the following raw materials and their weight percentages: 27% potassium feldspar, 9% quartz, 15% calcite, 4% aluminum powder, 27% Jiepai mud, and 18% colorant; the surface glaze of the medium-temperature double-layer kiln-changed glaze includes the following raw materials and their weight percentages: 52% boron frit, 11% quartz, 3% bone carbon, 5% spodumene, 11% zinc oxide, 7% talc, and 11% Jiepai mud. The patent discloses a formula for a bright double-layer glaze.
[0004] The Chinese patent application with publication number CN110790506A discloses a granular double-layer reaction glaze and a preparation method, which is a granular double-layer reaction glaze, comprising the following components and their respective weight parts: base glaze: 30-40 parts of albite, 5-15 parts of quartz, 5-15 parts of wollastonite, 2-6 parts of calcined alumina, 25-35 parts of kaolin, 15-25 parts of colorant; top glaze: 35-45 parts of high-boron frit, 15-25 parts of quartz, 5-10 parts of wollastonite, 5-15 parts of spodumene, 10-20 parts of calcined zinc oxide, 5-15 parts of kaolin, 5-10 parts of calcined talc, 5-10 parts of titanium dioxide, and 5-15 parts of zirconium silicate; the sintering time of the present invention is short, and it has high thermal shock resistance and glaze surface hardness. The patent also discloses a bright glaze.
[0005] Therefore, it is urgent to develop a medium-temperature matte double-layer kiln-changed glaze and a preparation method thereof to meet the current market demand. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a medium-temperature matte double-layer kiln-changed glaze and a preparation method thereof, so as to obtain a matte double-layer kiln-changed glaze with low lead and cadmium content, good thermal shock resistance and low firing temperature.
[0007] The content of the present invention includes:
[0008] A medium-temperature matte double-layer kiln-changed glaze, the base glaze of which comprises the following raw materials in parts by weight: 8-12 parts of boron frit, 35-45 parts of potassium feldspar, 8-12 parts of quartz powder, 10-12 parts of calcite, 8-10 parts of wollastonite, 8-11 parts of alumina powder, 4-6 parts of burnt talc, 5-6 parts of burnt zinc, 5-6 parts of Guizhou soil, 5-7 parts of titanium dioxide, and 5-10 parts of colorant;
[0009] The surface glaze of the medium-temperature matte double-layer kiln-changed glaze includes the following raw materials in parts by weight: 25-35 parts of boron frit, 20-30 parts of potassium feldspar, 8-12 parts of quartz powder, 8-15 parts of calcite, 10-20 parts of wollastonite, 20-30 parts of dolomite, 20-30 parts of longyan soil, 5-10 parts of titanium dioxide, 3-8 parts of aluminum powder, and 1-5 parts of colorant.
[0010] The boron frit is a strong flux containing boron, which has the function of forming glass with other silicates and promoting phase separation, and can also reduce the high-temperature viscosity of the glaze and increase the glossiness of the glaze surface.
[0011] Table 1 Raw material composition
[0012]
[0013] In one embodiment, the base glaze of the medium-temperature matte double-layer kiln-changed glaze includes the following raw materials in parts by weight: 10 parts of boron frit, 40 parts of potassium feldspar, 10 parts of quartz powder, 10 parts of calcite, 10 parts of wollastonite, 9 parts of aluminum powder, 6 parts of burnt talc, 5 parts of burnt zinc, 5 parts of Guizhou soil, 5 parts of titanium dioxide, and 10 parts of colorant.
[0014] In one embodiment, the surface glaze of the medium-temperature matte double-layer kiln-changed glaze includes the following raw materials in parts by weight: 30 parts of boron frit, 25 parts of potassium feldspar, 10 parts of quartz powder, 10 parts of calcite, 15 parts of wollastonite, 25 parts of dolomite, 25 parts of longyan soil, 5 parts of titanium dioxide, 5 parts of aluminum powder, and 2 parts of colorant.
[0015] In one embodiment, the colorant is one of red iron oxide, manganese carbonate, cobalt oxide or copper oxide.
[0016] Another object of the present invention is to provide a method for preparing the above-mentioned medium-temperature matte double-layer kiln-changed glaze, comprising the following steps:
[0017] (1) Prepare the base glaze raw materials and the top glaze raw materials according to the raw materials and weights;
[0018] (2) wet-milling the base glaze raw materials and the top glaze raw materials respectively, and sieving to obtain base glaze slurry and top glaze slurry;
[0019] (3) Add water to adjust the concentration of the base glaze slurry and the top glaze slurry, then attach the base glaze slurry to the body, and then attach the top glaze slurry to the base glaze slurry to form a semi-finished product, dry it, and fire it in an oxidizing atmosphere at a firing temperature of 1230-1250°C to obtain a finished product.
[0020] In one embodiment, the fineness of the base glaze slurry and the top glaze slurry is 0.02-0.04% on a 250-mesh sieve.
[0021] In one embodiment, the concentration of the base glaze slurry is 40-45 degrees Baume, and the concentration of the top glaze slurry is 55-60 degrees Baume.
[0022] In one embodiment, the thickness of the base glaze is 0.1-0.2 mm, and the thickness of the top glaze is 0.05-0.1 mm.
[0023] In one embodiment, the base glaze slurry is attached to the body by dipping, glazing or spraying; the top glaze slurry is attached to the base glaze by spraying.
[0024] In one embodiment, the wet ball milling method is as follows: the ball milling time is 20-24 hours, the mass ratio of the ball milling raw materials: zirconium aluminum spherules: water is 1:1.5-2:0.5, and the weight ratio of large spherules, medium spherules, and small spherules in the zirconium aluminum spherules is 2:5:3.
[0025] Beneficial effects of the present invention:
[0026] (1) The base glaze of the present invention uses a relatively large amount of calcium aluminum titanium matte glaze layer to carry the kiln-fired effect of the top glaze. The top glaze is made of boron frit as the main material, with a large amount of dolomite and kaolin, an appropriate amount of titanium dioxide and calcined talc and a small amount of calcium. When the top glaze is in the initial melting state at high temperature, fine crystal spots are formed in the state of high calcium and magnesium matte glaze due to the effect of titanium dioxide. Furthermore, the top glaze is mainly made of boron frit and has a lower initial melting temperature and a lower high temperature viscosity, while the base glaze has a higher initial melting temperature and high calcium aluminum, etc., which form different crystals under the action of titanium dioxide and react to release a large amount of gas at high temperature. Under high temperature, the gas breaks through the top glaze in the initial melting state, disturbs the glaze layer, increases the flow of the glaze layer, and forms fine patterns of different sizes. Under the dissolving action of the top glaze, some of the metal oxides of the base glaze penetrate into the top glaze, and fine patterns of different colors are produced due to the different solubility of the top glaze for various metal oxides.
[0027] (2) The present invention improves the process of adding bottom glaze to top glaze and strictly controls the formula composition of bottom glaze and top glaze, thereby increasing the bonding between the body and the glaze, greatly improving the thermal shock resistance and the firing range, and controlling the addition amount of key components to increase the flow of the glaze layer to form fine patterns of varying sizes and form a kiln-changed effect;
[0028] (3) The thermal stability and lead and cadmium dissolution of the matte double-layer kiln-changed glaze product of the present invention meet the daily-use porcelain standards of the country and the exporting countries; the product firing system of the present invention does not require firing in a specific kiln and is suitable for large-scale production;
[0029] (4) The present invention mainly uses the kiln-changed glaze of uniform porcelain as the top glaze of the double-layer glaze, and designs a matching bottom glaze to achieve a perfect combination of the artistry and color richness of the glaze. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The medium-temperature matte double-layer kiln-changed glaze prepared in Example 1 of the present invention;
[0031] Figure 2 The medium-temperature matte double-layer kiln-changed glaze is prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0032] Example 1
[0033] The formula components and contents of the present invention are:
[0034] Base glaze: 10 parts by weight of boron frit from Liling, 40 parts by weight of potassium feldspar from Hubei, 10 parts by weight of quartz powder from Liling, 10 parts by weight of calcite from Guangxi, 10 parts by weight of wollastonite from Jiangxi, 9 parts by weight of alumina powder from Zhengzhou, 6 parts by weight of burned talc from Guangxi, 5 parts by weight of burned zinc from Guiyang, 5 parts by weight of special Guizhou soil from Guizhou, 5 parts by weight of titanium dioxide from Zhuzhou, 4 parts by weight of Golden Eagle vanadium zirconium blue, and 5 parts by weight of Golden Eagle spectrum yellow;
[0035] Top glaze: 30 parts by weight of boron frit from Liling, 25 parts by weight of potassium feldspar from Hubei, 10 parts by weight of quartz powder from Liling, 10 parts by weight of calcite from Guangxi, 15 parts by weight of wollastonite from Jiangxi, 25 parts by weight of dolomite from Guangxi, 25 parts by weight of soil from Longyan, Fujian, 5 parts by weight of titanium dioxide from Zhuzhou, 5 parts by weight of aluminum powder from Zhengzhou, and 2 parts by weight of copper oxide from Shanghai;
[0036] The production method of medium temperature matte double-layer kiln-changed glaze is:
[0037] 1. Prepare materials according to the components and their mass percentages, add the raw materials into a ball mill, add an appropriate amount of water, and wet-mill together for 22 hours to obtain a glaze with a fineness of 0.02-0.04% residue after passing through a 250-mesh sieve, and pass the glaze through a 120-mesh sieve to obtain a glaze slurry; wherein the mass ratio of raw materials: ball stone: water is 1:1.5:0.5, and the weight ratio of large ball stone, medium ball stone, and small ball stone in the zirconium aluminum ball stone is 2:5:3.
[0038] 2. Add water to adjust the concentration of the base glaze slurry to 40 degrees Baume, then use the dipping method to attach the base glaze to the body, and then spray the top glaze on the base glaze by spraying. Dry at 50℃ for 2 hours, and then fire the body in an oxidizing atmosphere with a maximum temperature of 1250℃ and a firing time of 7 hours. After firing, the finished product is obtained.
[0039] Example 2
[0040] The formula components and contents of the present invention are:
[0041] Base glaze: 12 parts by weight of boron frit from Liling, 40 parts by weight of potassium feldspar from Hubei, 10 parts by weight of quartz powder from Liling, 10 parts by weight of calcite from Guangxi, 10 parts by weight of wollastonite from Jiangxi, 10 parts by weight of alumina powder from Zhengzhou, 6 parts by weight of burned talc from Guangxi, 5 parts by weight of burned zinc from Guiyang, 5 parts by weight of special Guizhou soil from Guizhou, 6 parts by weight of titanium dioxide from Zhuzhou, 10 parts by weight of red iron oxide from Yantai, and 5 parts by weight of cobalt black from Golden Eagle;
[0042] Top glaze: 35 parts by weight of boron frit from Liling, 20 parts by weight of potassium feldspar from Hubei, 10 parts by weight of quartz powder from Liling, 10 parts by weight of calcite from Guangxi, 15 parts by weight of wollastonite from Jiangxi, 25 parts by weight of dolomite from Guangxi, 25 parts by weight of soil from Longyan, Fujian, 5 parts by weight of titanium dioxide from Zhuzhou, 4 parts by weight of aluminum powder from Zhengzhou, and 1 part by weight of cobalt black from Golden Eagle;
[0043] Production method of medium temperature matte double-layer kiln-changed glaze:
[0044] 1. Prepare materials according to the components and their mass percentages, add the raw materials into a ball mill, add an appropriate amount of water, and wet-mill together for 22 hours to obtain a glaze with a fineness of 0.02-0.04% residue after passing through a 250-mesh sieve, and pass the glaze through a 120-mesh sieve to obtain a glaze slurry; wherein the mass ratio of raw materials: ball stone: water is 1:2:0.5, and the weight ratio of large ball stone, medium ball stone, and small ball stone in the zirconium-aluminum ball stone is 2:5:3.
[0045] 2. Add water to adjust the concentration of the base glaze slurry to 42 degrees Baume, then use the method of dipping, glazing or spraying to attach the base glaze to the body, and then spray the top glaze on the base glaze. Dry at 45℃ for 2 hours, and then fire the body in an oxidizing atmosphere with a maximum temperature of 1250℃ and a firing time of 7 hours. After firing, the finished product is obtained.
[0046] Example 3
[0047] The formula components and contents of the present invention are:
[0048] Base glaze: 12 parts by weight of boron frit from Liling, 40 parts by weight of potassium feldspar from Hubei, 10 parts by weight of quartz powder from Liling, 10 parts by weight of calcite from Guangxi, 10 parts by weight of wollastonite from Jiangxi, 10 parts by weight of alumina powder from Zhengzhou, 6 parts by weight of burned talc from Guangxi, 5 parts by weight of burned zinc from Guiyang, 5 parts by weight of special Guizhou soil from Guizhou, 6 parts by weight of titanium dioxide from Zhuzhou, 3 parts by weight of cobalt black from Golden Eagle, and 2 parts by weight of copper oxide from Huafei;
[0049] Top glaze: 30 parts by weight of boron frit from Liling, 25 parts by weight of potassium feldspar from Hubei, 10 parts by weight of quartz powder from Liling, 10 parts by weight of calcite from Guangxi, 15 parts by weight of wollastonite from Jiangxi, 25 parts by weight of dolomite from Guangxi, 20 parts by weight of soil from Longyan, Fujian, 6 parts by weight of titanium dioxide from Zhuzhou, and 8 parts by weight of aluminum powder from Zhengzhou;
[0050] Method for making medium temperature double-layer kiln-changed glaze:
[0051] 1. Prepare materials according to the components and their mass percentages, add the raw materials into a ball mill, add an appropriate amount of water, and wet-mill together for 22 hours to obtain a glaze with a fineness of 0.02-0.04% residue after passing through a 250-mesh sieve, and pass the glaze through a 120-mesh sieve to obtain a glaze slurry; wherein the mass ratio of raw materials: ball stone: water is 1:2:0.5, and the weight ratio of large ball stone, medium ball stone, and small ball stone in the zirconium-aluminum ball stone is 2:5:3.
[0052] 2. Add water to adjust the concentration of the base glaze slurry to 40 degrees Baume, then use the method of dipping, glazing or spraying to attach the base glaze to the body, and then spray the top glaze on the base glaze. Dry at 60℃ for 2 hours, and then fire the body in an oxidizing atmosphere with a maximum temperature of 1250℃ and a firing time of 7 hours. After firing, the finished product is obtained.
[0053] Example 4
[0054] The base glaze is the same as in Example 1;
[0055] Top glaze: 25 parts by weight of boron frit from Liling, 30 parts by weight of potassium feldspar from Hubei, 8 parts by weight of quartz powder from Liling, 15 parts by weight of calcite from Guangxi, 10 parts by weight of wollastonite from Jiangxi, 20 parts by weight of dolomite from Guangxi, 30 parts by weight of soil from Longyan, Fujian, 10 parts by weight of titanium dioxide from Zhuzhou, 8 parts by weight of aluminum powder from Zhengzhou, and 2 parts by weight of copper oxide from Shanghai;
[0056] The preparation method is the same as that of Example 1.
[0057] Example 5
[0058] Base glaze: 8 parts by weight of boron frit from Liling, 42 parts by weight of potassium feldspar from Hubei, 11 parts by weight of quartz powder from Liling, 10 parts by weight of calcite from Guangxi, 10 parts by weight of wollastonite from Jiangxi, 8 parts by weight of alumina powder from Zhengzhou, 4 parts by weight of burned talc from Guangxi, 6 parts by weight of burned zinc from Guiyang, 5 parts by weight of special Guizhou soil from Guizhou, 7 parts by weight of titanium dioxide from Zhuzhou, 4 parts by weight of Golden Eagle vanadium zirconium blue, and 5 parts by weight of Golden Eagle spectrum yellow;
[0059] The glaze is the same as in Example 1;
[0060] The preparation method is the same as Example 1.
[0061] Comparative Example 1
[0062] The weight portion of Zhengzhou aluminum powder in the base glaze is 0 part, and the rest is the same as in Example 1.
[0063] Comparative Example 2
[0064] The content of titanium dioxide in the glaze is 0 part, and the rest is the same as in Example 1.
[0065] Comparative Example 3
[0066] The Liling boron frit in the base glaze is removed, and the rest is the same as in Example 1.
[0067] Comparative Example 4
[0068] The formula components and contents of the present invention are:
[0069] Base glaze: 15 parts by weight of boron frit from Liling, 30 parts by weight of potassium feldspar from Hubei, 6 parts by weight of quartz powder from Liling, 14 parts by weight of calcite from Guangxi, 10 parts by weight of wollastonite from Jiangxi, 6 parts by weight of alumina powder from Zhengzhou, 8 parts by weight of burned talc from Guangxi, 4 parts by weight of burned zinc from Guiyang, 7 parts by weight of special Guizhou soil from Guizhou, 8 parts by weight of titanium dioxide from Zhuzhou, 4 parts by weight of Golden Eagle vanadium zirconium blue, and 5 parts by weight of Golden Eagle spectrum yellow;
[0070] Top glaze: 40 parts by weight of boron frit from Liling, 15 parts by weight of potassium feldspar from Hubei, 15 parts by weight of quartz powder from Liling, 7 parts by weight of calcite from Guangxi, 8 parts by weight of wollastonite from Jiangxi, 30 parts by weight of dolomite from Guangxi, 15 parts by weight of soil from Longyan, Fujian, 3 parts by weight of titanium dioxide from Zhuzhou, 10 parts by weight of aluminum powder from Zhengzhou, and 2 parts by weight of copper oxide from Shanghai;
[0071] The rest is the same as in Example 1.
[0072] Comparative Example 5
[0073] Base glaze: 2 parts by weight of boron frit from Liling, 30 parts by weight of potassium feldspar from Hubei, 14 parts by weight of quartz powder from Liling, 5 parts by weight of calcite from Guangxi, 15 parts by weight of wollastonite from Jiangxi, 5 parts by weight of alumina powder from Zhengzhou, 10 parts by weight of burned talc from Guangxi, 8 parts by weight of burned zinc from Guiyang, 2 parts by weight of special Guizhou soil from Guizhou, 12 parts by weight of titanium dioxide from Zhuzhou, 4 parts by weight of Golden Eagle vanadium zirconium blue, and 5 parts by weight of Golden Eagle spectrum yellow;
[0074] Top glaze: 20 parts by weight of boron frit from Liling, 35 parts by weight of potassium feldspar from Hubei, 15 parts by weight of quartz powder from Liling, 15 parts by weight of calcite from Guangxi, 15 parts by weight of wollastonite from Jiangxi, 35 parts by weight of dolomite from Guangxi, 10 parts by weight of soil from Longyan, Fujian, 8 parts by weight of titanium dioxide from Zhuzhou, 2 parts by weight of aluminum powder from Zhengzhou, and 2 parts by weight of copper oxide from Shanghai;
[0075] The rest is the same as in Example 1.
[0076] In order to illustrate the performance of the ceramics of the present application, the applicant tested the products of Examples 1-5 and Comparative Examples 1-5 and obtained the test data shown in Table 2.
[0077] Table 2 Ceramic performance test table of different products
[0078]
[0079]
[0080] The lead-cadmium capacity detection method of the present invention is ASTM C738-94 (Reapproved 2011), and the thermal stability detection method is GB / T3298-2008.
[0081] Examples 1-5 are medium-temperature matte double-layer kiln-changed glaze formulas within the scope of this application. The obtained products have clear lines, matte glaze surface, and fine or mesh textures.
[0082] No Zhengzhou aluminum powder is added to the base glaze of Comparative Example 1. Aluminum powder is used to prepare matte glaze and also serves as a medium for color layer analysis in glaze. No aluminum powder is added to the base glaze of Comparative Example 1, resulting in slight brewing on the glaze surface, bright glaze surface, and no kiln-changing effect.
[0083] In the glaze of Comparative Example 2, no titanium dioxide is added, which changes the chemical composition of the glaze formula, resulting in no kiln-changing effect and also affecting the formation of fine crystal spots in the glaze.
[0084] No Liling boron frit is added to the base glaze of Comparative Example 3. The function of boron frit in ceramic glaze is to quickly mature and form a smooth glaze layer. No boron frit is added to the base glaze, resulting in a dull glaze surface and no obvious kiln-changing effect.
[0085] In the base glaze and top glaze formula of Comparative Example 4, boron frit, titanium dioxide and other ingredients were added, and components such as potassium feldspar and calcite were reduced, resulting in a brighter glaze surface and an unobvious reaction effect.
[0086] The base glaze and top glaze formulas of Comparative Example 5 reduced ingredients such as boron frit, resulting in an excessively matte glaze surface with a bubble phenomenon.
[0087] A person skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of protection of the present application is limited to these examples. In line with the concept of the present application, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of different aspects of one or more embodiments of the present application as described above, which are not provided in detail for the sake of simplicity.
[0088] One or more embodiments of the present application are intended to cover all such substitutions, modifications and variations that fall within the broad scope of the present application. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of one or more embodiments of the present application should be included in the protection scope of the present application.
Claims
1. A medium-temperature matte double-layer kiln-changed glaze, characterized in that: The base glaze of the medium-temperature matte double-layer kiln-changed glaze comprises the following raw materials in parts by weight: 8-12 parts of boron frit, 35-45 parts of potassium feldspar, 8-12 parts of quartz powder, 10-12 parts of calcite, 8-10 parts of wollastonite, 8-11 parts of alumina powder, 4-6 parts of burnt talc, 5-6 parts of burnt zinc, 5-6 parts of Guizhou soil, 5-7 parts of titanium dioxide, and 5-10 parts of colorant; The surface glaze of the medium-temperature matte double-layer kiln-changed glaze includes the following raw materials in parts by weight: 25-35 parts of boron frit, 20-30 parts of potassium feldspar, 8-12 parts of quartz powder, 8-15 parts of calcite, 10-20 parts of wollastonite, 20-30 parts of dolomite, 20-30 parts of longyan soil, 5-10 parts of titanium dioxide, 3-8 parts of aluminum powder, and 1-5 parts of colorant.
2. The medium-temperature matte double-layer kiln-changed glaze according to claim 1 is characterized in that: The base glaze of the medium-temperature matte double-layer kiln-changed glaze includes the following raw materials in parts by weight: 10 parts of boron frit, 40 parts of potassium feldspar, 10 parts of quartz powder, 10 parts of calcite, 10 parts of wollastonite, 9 parts of aluminum powder, 6 parts of burned talc, 5 parts of burned zinc, 5 parts of Guizhou soil, 5 parts of titanium dioxide, and 10 parts of colorant.
3. The medium-temperature matte double-layer kiln-changed glaze according to claim 1 is characterized in that: The surface glaze of the medium-temperature matte double-layer kiln-changed glaze includes the following raw materials in parts by weight: 30 parts of boron frit, 25 parts of potassium feldspar, 10 parts of quartz powder, 10 parts of calcite, 15 parts of wollastonite, 25 parts of dolomite, 25 parts of longyan soil, 5 parts of titanium dioxide, 5 parts of aluminum powder, and 2 parts of colorant.
4. The medium-temperature matte double-layer kiln-changed glaze according to any one of claims 1 to 3, characterized in that: The colorant is one of red iron oxide, manganese carbonate, cobalt oxide or copper oxide.
5. A method for preparing the medium-temperature matte double-layer kiln-changed glaze according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Prepare the base glaze raw materials and the top glaze raw materials according to the raw materials and weights; (2) wet-milling the base glaze raw materials and the top glaze raw materials respectively, and sieving to obtain base glaze slurry and top glaze slurry; (3) Add water to adjust the concentration of the base glaze slurry and the top glaze slurry, then attach the base glaze slurry to the body, and then attach the top glaze slurry to the base glaze slurry to form a semi-finished product, dry it, and fire it in an oxidizing atmosphere at a firing temperature of 1230-1250°C to obtain a finished product.
6. The method for preparing the medium-temperature matte double-layer kiln-changed glaze according to claim 5, characterized in that: The fineness of the base glaze slurry and the top glaze slurry is 0.02-0.04% on a 250-mesh sieve.
7. The method for preparing the medium-temperature matte double-layer kiln-changed glaze according to claim 5, characterized in that: The concentration of the base glaze slurry is 40-45 degrees Baume, and the concentration of the top glaze slurry is 55-60 degrees Baume.
8. The method for preparing the medium-temperature matte double-layer kiln-changed glaze according to claim 5, characterized in that: The thickness of the bottom glaze is 0.1-0.2 mm, and the thickness of the top glaze is 0.05-0.1 mm.
9. The method for preparing the medium-temperature matte double-layer kiln-changed glaze according to claim 5, characterized in that: The base glaze slurry is attached to the body by dipping, glazing or spraying; the top glaze slurry is attached to the base glaze by spraying.
10. The method for preparing the medium-temperature matte double-layer kiln-changed glaze according to any one of claims 5 to 9, characterized in that: The wet ball milling method is as follows: the ball milling time is 20-24 hours, the mass ratio of the ball milling raw materials: zirconium aluminum spherules: water is 1:1.5-2:0.5, and the weight ratio of large spherules, medium spherules, and small spherules in the zirconium aluminum spherules is 2:5:3.
Citation Information
Patent Citations
Low-temperature matte reaction glaze and production method thereof
CN105130193A
Double-layer pearl reaction glaze and preparation method thereof
CN111233331A
Blue composite transmutation glaze material and method for preparing transmutation glaze ceramic by adopting glaze material
CN112079570A
Double-layer flow difference reaction glaze and preparation method
CN112645597A
Medium-temperature double-layer transmutation fancy glaze and manufacturing method thereof
CN113800770A
